Analisis Perbandingan Persepsi Tenaga Non PNS Mengenai Profesionalisme Pada Instansi BLUD Dan OPD Di Kutai Kartanegara (Studi Kasus Pada RSUD A.M Parikesit Dan Dinas Pekerjaan Umum) - Nurhayati, Dayang Dessy; Luthman, Awang Yacoub; Mulyadi, Dedy (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:The purpose of this study was to find out whether there were differences in the professionalism of work of Non PNS employees at BLUD Institutions with OPD in Kutai Kartanegara. The data used is primary data. This research method uses incidental sampling. The sample studied was 86 respondents in BLUD and 52 respondents in OPD. The number of variables studied is 1 namely work professionalism with 5 indicators. In this study, the Independent Sample T-Test Test was analyzed by comparing the mean values of BLUDs and OPDs in Kutai Kartanegara. From the results of the study stated that the statement of the first hypothesis in this study which states "that there are differences in the professionalism of the work of Non PNS employees in BLUD Institutions with OPD in Kutai Kartanegara" accepted. This is reinforced by the results of the Independent Sample T-Test which obtained a tcount of 12.902 with a probability (Sig.) 0,000 which is also smaller than 0.05. Then the statement from the second hypothesis which states "that the professionalism of the work of Non PNS employees at BLUD Agencies is higher than the OPD in Kutai Kartanegara" is accepted. It is proven by the results of the comparison of the average value obtained by the mean value of the BLUD 23.2558, while the mean value on the OPD is smaller which is equal to 20.0192.Keywords: Work Professionalism